REPURCHASE INTENTION ANALYSIS ON DECISION MAKERS IN PURCHASING MEETING PACKAGE AT BUSINESS HOTEL IN BANDUNG - Kani, Eiza Maghfira; Kusumah, Ahmad Hudaiby Galih; Wirakusuma, Reiza Miftah (Journal of Indonesian Tourism, Hospitality and Recreation)
The MICE (Meeting, Incentive, Convention, and Exhibition) industry is set by the government as the flagship product of national tourism. This is because the MICE industry is also the top five contributors or the top 5 contributors along with shopping, culinary, heritage, and religious tourism. This research focuses on meeting packages at hotels in Bandung City which is also one of the supporting facilities for this sector. Analysis of repurchase intention is done to find out how big the level of a decision maker to conduct a meeting at a business hotel in Bandung. This research is important to know what things can increase their desire for repeat purchase that affects occupancy. The purpose of this study is also to find out what is the motivation of repurchase intention, along with its elements. In its implementation, this research used content analysis method and looked for information with semi-structured interview to 10 people. The results of this study indicate that repurchase intention is formed by the pull factor and the driving factor formed from 11 constituent elements, namely satisfaction, company policy, novelty seeking, pricing, facilities, location, F & B products, service, hotel image, bonus & privilege, and flexibility.Keywords: repurchase intentions, hotel meeting packages, intrinsic and push & pull factors